Visual Learning With Canva: Meningkatkan Literasi Digital Siswa Dengan Media Desain Interaktif di SMA 23 Makassar - Sulolipu, Andi Annisa; Rosmayanti, Vivit; Wahid, Areski; Ram, St. Wijdanah; Ishak, Suryadi (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Digital literacy is an essential ability that students must have to face the challenges of the digital era. However, many students still use technology passively without developing creative and productive skills. The "Visual Learning with Canva: Increasing Students' Digital Literacy with Interactive Design Media at SMA 23 Makassar" program aims to increase students' digital literacy through a design-based learning approach. Students will learn to create visual content such as posters, infographics, and presentations that are relevant to learning. This training integrates digital literacy, creativity, and critical thinking skills as provisions for students to improve their learning abilities. The expected results of this training are an increase in students' ability to understand and use technology productively, as well as the creation of quality visual content that can support the learning process and increase participants' digital literacy.